A criterion for the formation of high entropy alloys based on lattice distortion. (April 2016) - Toda-Caraballo, I.; Rivera-Díaz-del-Castillo, P.E.J.
Abstract: Lattice distortion in high entropy alloys (HEAs) is one of their main crystallographic features. Its description is possible by means of unit cell parameter and bulk modulus variations of their constituent elements. The balance of forces acting on the lattice atoms under such distortion is related to the formation of a solid solution of a given crystal structure. This leads to the definition of a novel criterion for selecting HEA compositions. The main existing families of HEAs have been classified under this approach, in addition to an extensive list of multicomponent alloys including intermetallics and bulk metallic glasses. Criteria reported in the literature have been revised with the multicomponent alloy database used in this work which, together with the proposed approach, can be used to improve our understanding of HEAs formation. Highlights: An analysis of the HEA existing families which shows their trends has been made. A description of the lattice distortion in multicomponent alloys is presented. The interatomic spacing and bulk modulus mismatch: new parameters to identify HEAs. A region between these two parameters separates HEAs from BMGs or intermetallics. The bulk modulus mismatch is related to the crystal structure a solid solution.